Impact of liquidity ratios on firm profitability (case of technology companies in Malaysia) / Muhammad Anwar Mohammad A'zlan - Mohammad A'zlan, Muhammad Anwar (2018)
The purpose of this study is to investigate the impact of liquidity ratios toward firm profitability. This is to make sure the firm have ability to maintain their daily operations. The data for this research consist about ten companies with the number of year are five year each. The data gather through the Thomson Reuters. The data was analysed to evaluate the impact of liquidity ratio toward firm profitability that can influence the company performance. The liquidity ratios consist of current ratio, quick ratio, and liquid ratio while the profitability ratios consist of return on asset. The final result show that only one variables which is liquid ratio that are significant with the return on assets while the other two variables known as current ratio and quick ratio are not significant with the return on assets. The levels of profitability of the company have attracted the intention of stakeholder. The supplier of good for the company will check the company liquidity performance to know whether the company able to pay their obligations toward their employee before making any transaction. Thus, the company need to pay full attention about the company liquidity performance due to the effect of toward company profit and the portion of dividend for the shareholder.